Cerebellar disruption impairs working memory during evidence accumulation - Ben Deverett (Nature Portfolio, 2019)
Disruption of cerebellar activity impairs working memory during evidence accumulation in mice. Here, the authors show that optogenetic perturbation of Purkinje cell activity disrupts the accurate accumulation of somatosensory information in working memory during perceptual decision-making.